THE OPTICAL AND RADIATING PROPERTIES KDP ACTIVATED BY IONS OF THALLIUM - Koketayev Т.А.; Kim, L.M.; Tagaeva, B.S.; Baltabekov А.S. (Recent Contributions to Physics, 2008)
In this work the study of optical, luminescent properties and thermoluminescence of crystals KDP doped by tallium ions in a temperature range 80-400К is carried out. It is established that the impurity ions are the centres of small radius. At irradiation they change the charging condition and the centres Tl2 + are formed.